The Relationship Between Conspiracy Mentality, Personality Traits, Stress Coping Strategies and Psychological Well-Being - Jucevičiūtė, Emilija; Zamalijeva, Olga; Giedraitytė, Miglė (Psichologija, 2024)
Conspiracy theories and people’s tendency to believe them have recently attracted a great deal of scientific attention because of the widespread nature of conspiracy beliefs, their potential to influence people’s behaviour and endanger public safety. To understand what leads people to believe in conspiracies, it is important to consider both intrinsic personal factors as well as external, learned factors that are related to the person’s environment. This study aims to explore which psychological factors contribute directly and indirectly to the propensity to believe conspiracy theories. The study involved 173 participants (80.3% women). The age of the participants ranged from 18 to 70 years (M = 33.34; SD = 14.62). The Conspiracy mentality scale was used to measure the subjects’ general tendency to believe in conspiracy theories. The participants’ Big Five personality traits, psychological well-being, and stress coping strategies were also assessed. The results of linear regression and path analysis show that the propensity to believe in conspiracy theories is directly predicted by social well-being, religion and avoidance coping which are used to reduce stress. In addition, conspiracy mentality has been found to be indirectly predicted by personality traits of extraversion and neuroticism, through social well-being and avoidance coping; in addition, path analysis revealed direct associations between the tendency to believe in conspiracy and extraversion. Skepticism (one of conspiracy mentality subscales) is directly predicted by avoidance coping strategy. Extraversion predicts propensity to believe conspiracy theories directly and – together with neuroticism – indirectly through social well-being and avoidance coping.